If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9=7p-5p+7
We simplify the equation to the form, which is simple to understand
9=7p-5p+7
We move all terms containing p to the left and all other terms to the right.
-7p+5p=+7-9
We simplify left and right side of the equation.
-2p=-2
We divide both sides of the equation by -2 to get p.
p=1
| y^2=10-6x^2 | | 9x-4=3x-16 | | 3x+5+6x-2=39 | | 4x^3-9x^2+6x=0 | | -2n=3n | | 5n-10=0 | | 40r+48s= | | 9r^2-49=0 | | -6(8+4n)+5(1+4n)=-11 | | 5(b-4)=12 | | -6(8+4n)+5(1+4n)=-1 | | p+.33p=.67 | | 41*8.98= | | 2r^2+7r^2-2r^2= | | x^2-x-14=3x-2 | | 3x+34-x+3=1 | | 8(5k-4)+3(-8k-6)=30 | | 2x^2+16x+42=0 | | 7(2-x)=5x | | 4x^7-20x^6+8x^5=0 | | 8(y-2)+6=2(y+1) | | x^2+6x+13=5 | | 3(2x-4)=3 | | 3w^2+12w+30=0 | | 12(7c+2)= | | Solvey=2x-3 | | x^2+2x=-10 | | 6.7x-4+3x-1.9= | | 0.5(2x+8)=5 | | ln(x+2)+ln(x+1)=0 | | 5g-5-8-5g= | | 16(3-d)=-4 |